Elephantgrass breeding focused on persistence and discover candidate genes - Rocha, João Romero do Amaral Santos de Carvalho (2019)
Due to environmental issues the world has been concerned with developing hazard mitigation plans. In the context of alternative energies, the biomass is studied from several candidate species (dedicated energy crops). Elephantgrass has been a notable option as a multi-purpose crop, e.g. bio-based products, co-products and biofuels, besides being used for animal feeding, this is mainly due to high photosynthetic efficiency, high biomass production, longevity, rapid growth, broad adaptation, desirable chemical properties and persistence. Regardless breeding efforts are imperative to contribute to Brazilian energetic matrix and animal production. To the best of our knowledge, in the bioenergy context, there are private companies that already installed in Brazil to use elephantgrass biomass to generate electricity (by the combustion of biomass) with installed capacity sufficient to supply a city with 200 thousand inhabitants of energy demand. While in the animal feeding context, it has been reported that the biomass digestibility can impact the animal performance since a small increase in dry matter digestibility (1%) can increase the daily weight gains in 3.2% for beef cattle. The first chapter (Genetic insights into elephantgrass persistence for bioenergy purpose) focused on assessing the biomass yield persistence for bioenergy purpose of 100 elephantgrass clones measured in six growth seasons in Brazil. To assess the clones' persistence, an index based on random regression models and genotype-ideotype distance was proposed. Results suggested the existence of wide genetic variability between elephantgrass clones, and that the yield trajectories along the harvests generate genetic insights into elephantgrass clones’ persistence and G x E interaction. A gene pool that acts over the biomass yield (regardless of the harvest) was detected, as well as other gene pools, which show differences on genes expression (these genes are the major responsible for clones’ persistence).It is noteworthy that the methodology used (random regression models) is adequate to achieve the aim of the work, as well as it can be applied with advantages in the study of the adaptability and stability of any crop when compared with the methodologies until now used. The second chapter (Discovering candidate genes underlying biomass digestibility in elephantgrass) brings information about the first trait-marker association study reported for the elephantgrass. It was compared the single-step genome-based best linear unbiased prediction (ssGBLUP - including the genomic relationship) and the simple repeatability plus genotypes by cuttings interaction models. It was verified that genomic information allowed increases the accuracy for biomass quality traits on elephantgrass, even with a small number of markers. We found two SSR markers associated to biomass digestibility and several candidate genes that have functions involved in biosynthesis of cell wall molecules. These markers are relevant and their use can be crucial to accelerate the elephantgrass genetic breeding. In this sense, identify candidate genes that can be used through marker-assisted selection can help to develop selection procedures that optimize elephant grass breeding for different uses.